MINHO@home - Ribeiro, A. Fernando (2010)
This paper briefly describes the development of a mobile robot to participate on RoboCup@Home. The focus of this project is to integrate robotic knowledge into home applications and human interaction. The robot has the ability to move in all directions due to its omnidirectional system with 3 Swedish wheels at 120º angle and can handle objects using an articulated arm with six degrees of freedom. It incorporates several vision systems allowing the robot to recognize faces and objects and to move autonomously on a domestic environment. Voice recognition and speech capabilities are also present.